IMPROVING KNOWLEDGE ON CHILD MARRIAGE THROUGH SYNCHRONOUS LEARNING IN TANJUNGAN VILLAGE, MOJOKERTO, INDONESIA - Doman, Zahras Azimuth; d'Arqom, Annette; Nasution, Mhd Zamal (Universitas Airlangga, 2025)
Child marriage remains a prevalent issue in many regions, including Indonesia. This practice is associated with significant adverse outcomes, such as interrupted education, elevated maternal morbidity and mortality rates, and prolonged the cycle of poverty. Synchronous learning can foster critical thinking, enabling audience to challenge harmful social norms and traditions that perpetuate child marriage. Thus, to this study aims to improve knowledge about child marriage among residents of Tanjungan Village, Mojokerto, through synchronous learning interventions. By employing a mixed-methods research design, a survey and interview following a synchronous learning from six experts on child marriage, the study explores the current understanding of respondents' knowledge of the minimum marriage age, the effects of child marriage, and evaluates the effectiveness of synchronous learning programs in enhancing knowledge towards delaying marriage. Sixty-five adolescents and adults from Tanjungan Village, Mojokerto District, East Java, participated in synchronous learning on regulation of child marriage and its consequences. A questionnaire is distributed to assess their knowledge of government regulations on the minimum age of marriage, minimum and maximum age of marriage, and age disparity during marriage before and after the activity followed by interviews with five participants, whom willing to be interviewed, to further explore their understanding of child marriage. The results show an increase in knowledge of the legal age for marriage (from 89.23% to 100%), with females demonstrating a higher level of understanding of this regulation. Interestingly, after the intervention, respondents' understanding of the maximum age limit for marriage varied more, with the majority suggesting ages between 21 and 26. These findings suggest that direct learning interventions can be effective in increasing awareness about child marriage, particularly regarding legal age limits. However, further research is needed to explore the long-term impact of these interventions and to develop strategies to address the underlying social and cultural factors that contribute to child marriage.